“Rehabilitación del desarrollo del control cefálico en niños menores de 3 años con retraso psicomotor mediante ejercicios fisioterapéuticos de la unidad educativa especializada “Carlos Garbay” periodo abril - septiembre 2016”. - Aguilar Guevara, Jennifer Paulina (2017)
Physiotherapeutic intervention in children with psychomotor retardation who regularly attend the Carlos Garbay Specialized Educational School was carried out in the period April-September 2016, using assessment sheets as instrument for collecting information. Through data collected, it was possible to determine the psychomotor retardation in children under three years of this institution. Research started by analyzing and understanding the different protocols of physiotherapeutic intervention, punctuating the concepts of psychomotor retardation, which is described to a sequence of physiotherapeutic exercises based on the of the child development. Every child has specific characteristics that define his specific psychomotor development. The aspects of the brain, musculoskeletal disorders and associated medical problems are the most significant factors involved in psychomotor development, both in relation to timing and quality of movement. The main purpose of the physiotherapeutic intervention is to optimize and accompany the childrens development, enhancing their abilities and taking into account their individuality. The child is given the opportunity to experience movement appropriately, providing optimal patterns, ensuring that patterns do not appear in misalignment and advising parents and other people in their environment. In the research there was a population of 13 children under 3 years of age in which 100% had a delay in their psychomotor development, corresponding to 53.85% of children and 46.15% of girls. The highest percentage of children were aged between 6 and 9 months (23.08%), while the lowest percentage were those aged 0 to 3 months (7.7%) and 3 to 6 months (7.7%), respectively. Among the main causes of psychomotor retardation were: Down syndrome (38.47%), fetal distress (23.07%), premature infants (23.07%) and low birth weight (15.39%). 61.54% of the children were hypotonic, 30.76% hypertonic, while 7.70% had a fluctuating tone. The delay of the psychomotor development was defined by Aicardi in 1998 as the delay in acquiring the proper skills for the age of the child,. An early detection allows to look for alternatives. This notion implies, as an interim diagnosis, that the developmental successes of slow sequence for the childs age, and this refers to the first milestones throughout the months of life, to the infant and toddler's motor skills. But, at present evolutionary semiology has been greatly enriched by the evaluation of the sensory, cognitive and interactive aptitudes of the subject, suitably integrated . Taking into account this concept we can mention that the psychomotor retardation refers to the deficit of the skills that the child performs according to his age. Through a series of physiotherapeutic exercises in the final evaluation, 92.30% showed cephalic control. Taking these results into consideration, it was possible to rehabilitate the psychomotor development of children under 3 years of age who attended the Carlos Garbay Specialized Education Unit in the period April-September 2016, through the practice of physiotherapeutic exercises, which in turn guaranteed independence, safety And confidence in infants in carrying out activities appropriate to their age.